Enhancing Theoretical Fidelity: An E-mail—Based Walking Program Demonstration - Rovniak, Liza S.; Hovell, Melbourne F.; Wojcik, Janet R.; Winett, Richard A.; Martinez-Donate, Ana P. (American journal of health promotion, 2005)
Purpose. To examine the extent to which theoretical fidelity, or precision in replicating theory-based recommendations, influenced the effectiveness of two walking programs based on social cognitive theory (SCT). Design. Two-group randomized controlled trial. Setting. College town in Virginia. Subjects. Sixty-one sedentary adult women. Intervention. Two 12-week e-mail–based walking programs were compared. The high fidelity program was designed to more precisely follow SCT recommendations for operationalizing mastery procedures than the low fidelity program, which was designed to simulate how mastery procedures were operationalized in most existing SCT-based physical activity programs. Treatment contact and walking prescription were controlled across groups. Measures. The 1-mile walk test of physical fitness and SCT measures were completed at baseline and posttest. Self-reported walking quantity was assessed at baseline, posttest, and 1-year follow-up. Walking logs were completed during the program. Process evaluation measures were completed at posttest. Results. Fifty women completed the study. The high fidelity group improved more than twice as much as the low fidelity group on 1-mile walk test time (86 vs. 32 seconds, p < .05), goal setting (p < .05), and positive outcome expectations (p < .05) and reported greater program satisfaction (p < .01). Conclusion. Theoretical fidelity could advance the quality of physical activity interventions, which have often shown small effects.